Autonomic Nervous System Response to Psychosocial Stress in Anorexia Nervosa: A Cross-Sectional and Controlled Study - Schmalbach, Ileana; Herhaus, Benedict; Pässler, Sebastian; Runst, Sarah; Berth, Hendrik; Wolff, Silvia; Schmalbach, Bjarne; Petrowski, Katja (Frontiers in Psychology, 2021)
To foster understanding in the psychopathology of patients with anorexia nervosa (PAN) at the psychological and physiological level, standardized experimental studies on reliable biomarkers are needed, especially due to the lack of disorder-specific samples. To this end, the autonomic nervous system (ANS) response to a psychosocial stressor was investigated in n = 19 PAN (BMI: 18.7 ± 3.3 kg/m2), age, and gender-matched to n = 19 healthy controls (HC; BMI: 24.23± 3.0 kg/m2). For this purpose, heart rate (HR) and heart rate variability (HRV) parameters were assessed in a cross-sectional study design under two experimental conditions: 1) rest and 2) stress (Trier Social Stress Test). In addition, psychological indicators of stress were assessed. An 2x2x8 ANOVA demonstrated similar HR and HRV patterns (except LF-HRV) between PAN and HC at rest. Under stress, PAN (vs. HC) demonstrated a blunted HR (condition*time*group: F(2.91,104.98) = 9.326, p = .000, η2 = .206) and an attenuated HRV response (reduced SNS/PNS reactivity). Significant effects of stress appraisal (SA) and BMI on HRV-reactivity were revealed. SA on SDNN = Condition*time*SA = F(4.12,140.15) = 2.676, p = .033, η2 = .073. BMI on LF/HF-Ratio = Condition*time*BMI = F(3.53,60.16) = 3.339, p = .019, η2 = .164. Psychological indices suggested higher levels of chronic and appraised stress in PAN relative to HC. Additional analyses demonstrated that ED-symptoms are highly correlated with the latter constructs, as well as with psychological burden, but not with weight. Further, it was shown that abnormalities in reactivity persisted despite normalized ANS activity. Overall, we suggested that besides weight recovery, improvement in stress appraisal could be beneficial for cardiac health. In this light, a combination of therapy (e.g., development and activation of coping skills, cognitive reappraisal) and biofeedback training may improve treatment outcomes and regulate stress reactivity.